2018
DOI: 10.1002/solr.201800054
|View full text |Cite
|
Sign up to set email alerts
|

Environmental‐Friendly Urea Additive Induced Large Perovskite Grains for High Performance Inverted Solar Cells

Abstract: It is a challenge to grow perovskite films with large crystalline grains and a full coverage on the surface of an organic compound film by a solution process. Herein, we for the first time introduce environmental‐friendly urea into PbI2 precursor to mediate the perovskite film growth and crystallization on the top of PEODT:PSS for efficient inverted solar cells. This method attains high‐quality perovskite films with large‐size grains of over 2 μm and a full coverage. This enables us to fabricate the inverted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 42 publications
4
56
0
Order By: Relevance
“…The GDZO solution (12 mg mL −1 in trifluoroethanol) was spin‐coated on ITO at 2000 rpm 60 s. After thermal annealing at 100 °C for 15 min in air, GDZO film is formed. To investigate the morphology and surface wettability of GDZO, SEM, and contact angle of water measurements were performed, as shown in Figure (b–g) . Through the comparison of Figure (b) (ZnO film) and (e) (GDZO film), we can observe that GDZO film is more dense and smooth.…”
Section: Resultsmentioning
confidence: 99%
“…The GDZO solution (12 mg mL −1 in trifluoroethanol) was spin‐coated on ITO at 2000 rpm 60 s. After thermal annealing at 100 °C for 15 min in air, GDZO film is formed. To investigate the morphology and surface wettability of GDZO, SEM, and contact angle of water measurements were performed, as shown in Figure (b–g) . Through the comparison of Figure (b) (ZnO film) and (e) (GDZO film), we can observe that GDZO film is more dense and smooth.…”
Section: Resultsmentioning
confidence: 99%
“…[4] The I-V hysteresis in PSCs is related to the unbalanced photoexcited electrons and holes, ferroelectric polarization, ion migration, charge carrier trapping, transient capacitive current, and so on. [7][8][9][10][11] Thus, it would be highly demanded to obtain high-efficient, hysteresis-less even hysteresis-free, and simultaneously stable PSCs by developing an effective methodology for precise perovskite film amelioration.The addition of a tiny amount of chemical additives in the perovskite precursor solution has been widely demonstrated as one of the most effective strategies to control the crystallization process, [12,13] like grain size or morphology of perovskite thin film, thus enhancing the PCE of the PSC devices. It has been demonstrated that high-quality perovskite thin films play a vital role in obtaining highperformance PSCs with excellent stability since the surface morphology and crystallization behavior of perovskite thin films can significantly affect the photoelectric characteristics, such as the charge carrier mobility, charge separation and collection efficiencies, recombination mechanics, lifetime, and diffusion-length of perovskite thin films.…”
mentioning
confidence: 99%
“…In addition to the 3D perovskite related features, a diffraction signal at 12.5° originating from the (001) plane of the hexagonal PbI 2 is observed for the pristine film4 and a very weak signal at 11.6° originating from the yellow phase of FA‐based perovskite (δ‐FAPbI 3 ) is observed for TGA‐modified perovskite film 40. The addition of GA does not alter the crystal orientation relative to the pristine perovskite film, but the crystallinity is improved with the enhanced XRD intensity 41–43. In contrast, the addition of TGA affects the crystal orientation, resulting in an increased intensity of the (101) peak at 13.9° relative to the (211) peak at 31.4°, their ratio changes from 2.55 to 9.52 44.…”
Section: Resultsmentioning
confidence: 99%